SISTEM PENGEMBANGAN USAHA PEMBIBITAN DURIAN (Durio zibethinus) - Bahrun, Bahrun; Rohansyah, Rohansyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The sampling method for carrying out this research used the census method, by taking all members of the population as samples from the number of durian breeding farmers (2 people).\                The total cost for the grafted durian seedling business in Sebelimbingan Village is IDR. 56,130,653.81 with an average of Rp. 28,065,326.91//farmers. The production produced by the durian breeding business in Sebelimbingan Village was 24,800 stems with an average of 12,400 per farmer. The revenue obtained was IDR. 421,600,000.00 with an average of Rp. 210,800,000.00/farmer. The average profit obtained is IDR. 172,252,892.50//farmers.